Special issue: 12th International Chemical & Biological Engineering Conference - interfacing bio- and chemical engineering - F. Xavier Malcata (2015)
CHEMPOR 2014, the 12th International Chemical and Biological Engineering Conference, is the leading Portuguese event where research institutions, academia and industry meet to discuss recent and cutting-edge research areas on chemical and biological engineering, in an inspiring and dynamic atmosphere. It was held in Porto (Portugal) between 10th and 12th of September 2014, and was organized by the Department of Chemical Engineering, College of Engineering of the University of Porto, and the Portuguese Engineers Association.